The power of appreciation: promoting schoolchildren's health literacy. Issue 6 (3rd October 2016) - Kostenius, Catrine; Bergmark, Ulrika
Abstract : Purpose: The purpose of this paper is to explore Swedish children's positive experiences of health and well-being, and their thoughts on how health literacy can be promoted. Design/methodology/approach: Totally, 121 schoolchildren between the ages of 10 and 14 from three schools in two municipalities in the northern part of Sweden shared their lived experiences through individual written reflections. Findings: The phenomenological analysis resulted in one theme, appreciation as fuel for health and well-being, and four sub-themes: feeling a sense of belonging; being cared for by others; being respected and listened to; and feeling valued and confirmed. The understanding of the schoolchildren's experiences of health and well-being and their thoughts on how health literacy can be promoted revealed that appreciation in different forms is the key dimension of their experiences of health and well-being. Practical implications: The findings of this study point to the necessity of promoting health education that includes reflection and action-awareness of one's own and others' health as well as the competence to know how and when to improve their health. Such health education can contribute to the development of health literacy in young people, an essential skill for the twenty-first century. Originality/value: This study's originality is that the authors added the concepts of appreciative inquiry and student voice to the study of health literacy with children.